(untitled) (Revista Electrónica REDINE, 2018)
This research is to design a guide as a teaching resource for the application of remote sensing images based on competencies for the study of the geographical landscape in Yacambú National Park, with the aim of improving the quality of teaching practice in the General Media Education LB Maria Teresa Angulo, Yacambú extension, aimed at teachers of Citizenship and Social Sciences. They worked under the parameters of regional analysis through the application of images from remote sensors. documentaries, mapping, statistics and topographical sources, accompanied by a field visit were reviewed. It was evident in the classroom a positivist teaching practice with behavioral characteristics, which concludes an appropriate manner the use and application of the guidance to be a new teaching resource that allows a geographical study more easily and with better results to the community in general.